Why be happy when you could be normal? - Winterson, Jeanette, 1959- (New York : Grove Press, 2011)
This memoir is a tough-minded search for belonging, for love, an identity, a home, and a mother by the author of "Oranges Are Not the Only Fruit"--winner of the Whitbread First Novel award and the inspiration behind the award- winning BBC television adaptation "Oranges."
Keywords: Winterson, Jeanette, -- 1959-; Lesbians -- England -- Biography; Authors, English -- Biography; Mothers and daughters -- Biography